Fundamentals of Entrepreneurship ENT300 Euphoria Cafe Enterprise Cake And Bakery / Nurul Balqis Zakariah...[et al.] - Zakariah, Nurul Balqis; Sapri, Nurul Fasihah; Che Azmi, Nurul Hanis; Noorshahran, Nurul Natasha; Hamizan, Nor Adlina (2019)
Euphoria Café Enterprise is based on partnership which consists of five (5) members that hold important position in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 100,000 where the total contribution of each member is RM 20,000. We offer café products and services for customers, providing variety cakes and drinks that gives high satisfaction to consumer. Our customers were identified as students and staff who want to consume the product easily with affordable price of product. Euphoria Café Enterprise marketing strategy is to emphasize the quality and price of our products and services. We offer the affordable price because majority of our customer are the students. Thus, we develop marketing strategy that give attraction to customers to come to our café specially for student. Lastly, we expect that our café will become established in the near future because our target is to make our café is more well-known within our market locations and more demands. This will give us more advantages for us to open new branches at other universities.